Television News, Politics and Young People - Wayne, M. author. aut Link
IX, 235 p.
Keywords: Why are young people alienated from television news? This book argues that contemporary trends indicating deepening disconnection from news about public life reflect both problems in the way television news covers politics - the single biggest item on the news - and problems with the nature of politics itself under neo-liberal capitalism.